Book review: Caouette, D and Kapoor, D., editors, 2016. Beyond Colonialism, Development and Globalization: Social Movements and Critical Perspectives. (July 2019) - Singh, Chandni
Caouette, D and Kapoor, D., editors, 2016. Beyond Colonialism, Development and Globalization: Social Movements and Critical Perspectives . London: Zed Books. 292 pp. 28.95$, ISBN: 978-1-78360-584-2 pb